2021
DOI: 10.3389/fphar.2021.631835
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-H19 Drives Cardiomyocyte Senescence by Targeting miR-19a/socs1/p53 Axis

Abstract: Purpose: Cardiomyocyte senescence is associated with a progressive decline in cardiac physiological function and the risk of cardiovascular events. lncRNA H19 (H19), a well-known long noncoding RNA (lncRNA), is involved in the pathophysiological process of multiple cardiovascular disease such as heart failure, cardiac ischemia and fibrosis. However, the role of H19 in cardiomyocyte senescence remains to be further explored.Methods: Senescence-associated β-galactosidases (SA-β-gal) staining was used to detect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Normally, the somatic cells has a limited lifespan - they can be replicated (but limitedly) and finally undergo cellular senescence, which is the process of permanent cell cycle arrest. Cellular senescence is a cell protective mechanism that can be detected by measuring the SA-β-gal activity 52 , 53 . Several lines of evidence have reported that suppression of cellular senescence is associated with the enhanced carcinogenesis 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Normally, the somatic cells has a limited lifespan - they can be replicated (but limitedly) and finally undergo cellular senescence, which is the process of permanent cell cycle arrest. Cellular senescence is a cell protective mechanism that can be detected by measuring the SA-β-gal activity 52 , 53 . Several lines of evidence have reported that suppression of cellular senescence is associated with the enhanced carcinogenesis 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the regulation of p21 expression in cellular senescence, miR-17-92 cluster has been known to affect senescence by regulating several other genes, such as Smurf1 and SOSC1 [23,24]. Recently, disrupted oxidative homeostasis and high ROS level have been characterized in MSC senescence.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that H19 is causally implicated in the effects of H 2 O 2 and that the increased H19 by sequestering miR-22, a direct inhibitor of the lymphoid enhancing factor-1 (LEF1), could activate the downstream Wnt/β-catenin signaling contributing to degenerative events [264]. Similarly, the high H19 has been recently implicated in cardiomyocyte senescence functioning as a ceRNA for miR-19a [265]. In this work, Zhuang et al demonstrate that the increase of H19, by scavenging miR-19a, consequently upregulated the suppressor of cytokine signaling 1 (SOCS1) expression (a target of this miRNA), thus enhancing the p53/p21 pathway [265].…”
Section: Long Rnas (Lncrnas)mentioning
confidence: 99%